KAJIAN FEMINISME DALAM SERIAL DRAMA AKU BUKAN USTAZAH KARYA IDORA ABDUL RAHMAN - Trimilati, Mita Latifa Intan; Heryana, Nanang; Wartiningsih, Agus (Universitas Tanjungpura, 2024)
This research aims to examine feminism in the drama series Aku Bukan Ustazah by Idora Abdul Rahman. The theory used is feminism with descriptive methods and a qualitative approach. The data source is in the form of stills and dialogue in the series that reflect gender inequality and the role of women. The data collection technique used documentary studies, producing 73 data related to issues such as marginalization, subordination, stereotypes, violence, workload, and the role of women in the family, as mothers and as wives. The findings of this research reveal how these issues are depicted in the narrative and characters of drama series. The results of this research are integrated with Indonesian language learning in class VIII of the Independent Curriculum Middle School through a teaching module that focuses on reviewing works of fiction. In this way, students not only understand fictional texts but are also able to analyze relevant social issues, so that learning becomes more contextual and meaningful.